Microstructure, ionic conductivity and mechanical properties of tape-cast Li1.5Al0.5Ti1.5P3O12 electrolyte sheets. Issue 5 (May 2020) - Dashjav, Enkhtsetseg; Gellert, Michael; Yan, Gang; Grüner, Daniel; Kaiser, Nico; Spannenberger, Stefan; Kraleva, Irina; Bermejo, Raul; Gerhards, Marie-Theres; Ma, Qianli; Malzbender, Jürgen; Roling, Bernhard; et al.
Highlights: Highly dense LATP (99.8%) sheets were prepared by tape casting. The ionic conductivity and mechanical properties were optimized by sintering addition of SiO2 . Relationship between the mechanical measurement and microstructures of were discussed. Abstract: Free-standing Li1.5 Al0.5 Ti1.5 P3 O12 electrolyte sheets with a thickness of 50–150 μm were prepared by tape casting followed by sintering at 850–1000 °C in air. While a sintering temperature of 850 °C was too low to achieve appreciable densification and grain growth, a peak relative density of 95% was obtained at 920 °C. At higher sintering temperatures, the microstructure changed from a bimodal grain size distribution towards exclusively large grains (> 10 μm), accompanied by a decrease in relative density (down to 86% at 1000 °C). In contrast, ionic conductivity increased with increasing sintering temperature, from 0.1 mS/cm at 920 °C to 0.3 mS/cm at 1000 °C. Sintering behavior was improved by adding 1.5% of amorphous silica to the slurry. In this way, almost full densification (99.8%) and an ionic conductivity of 0.2 mS/cm was achieved at 920 °C. Mechanical characterization was carried out on the almost fully densified material, yielding elastic modulus and hardness values of 109 and 8.7 GPa, respectively. The fracture strength and Weibull modulus were also characterized. The results confirm that densification and reduction of grain size improve the mechanical properties.